The ILRI Board Position on the New CGIAR - International Livestock Research Institute (International Livestock Research Institute, 2009)
The Board of Trustees of the International Livestock Research Institute (ILRI) met from 9-11 November 2009 in Addis Ababa, Ethiopia. The Board reviewed progress made in the CGIAR change process during the course of Alliance and ExCo meetings held in Rome in late October/early November. The Board considered the potential impact of ongoing and proposed changes on ILRI’s mandate. We also reflected on the role that ILRI might play, going forward, in helping to shape the new Consortium of CGIAR-supported centers as an effective global leader in agricultural research for development.